2016
DOI: 10.1371/journal.pmed.1002036
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening the Reporting of Observational Studies in Epidemiology—Nutritional Epidemiology (STROBE-nut): An Extension of the STROBE Statement

Abstract: BackgroundConcerns have been raised about the quality of reporting in nutritional epidemiology. Research reporting guidelines such as the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) statement can improve quality of reporting in observational studies. Herein, we propose recommendations for reporting nutritional epidemiology and dietary assessment research by extending the STROBE statement into Strengthening the Reporting of Observational Studies in Epidemiology—Nutritional Epid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
192
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 320 publications
(221 citation statements)
references
References 23 publications
6
192
0
1
Order By: Relevance
“…Lastly, only four of the 35 studies had a positive risk of bias assessment score indicating that future nutrition research needs stronger design and reporting strategies. The Strobe-NUT [79] reporting guidelines are aimed at improving the reporting of observational studies with a focus on diet and health and should be employed in future research to increase transparency and consistency of nutritional epidemiology studies.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, only four of the 35 studies had a positive risk of bias assessment score indicating that future nutrition research needs stronger design and reporting strategies. The Strobe-NUT [79] reporting guidelines are aimed at improving the reporting of observational studies with a focus on diet and health and should be employed in future research to increase transparency and consistency of nutritional epidemiology studies.…”
Section: Discussionmentioning
confidence: 99%
“…This study is reported according to the Strengthening the Reporting of Observational Studies in Nutritional Epidemiology (STROBE-nut) guidelines [27] (see Supplementary Method S1: STROBE-nut statement).…”
Section: Methodsmentioning
confidence: 99%
“…The current analysis specifically focused on mental health and dietary intake data. The study conduct and reporting were compliant with STROBE-nut guidelines [34].…”
Section: Methodsmentioning
confidence: 99%
“…The cut points for the AUDIT include abstinence/low risk (0-7), moderate risk (8)(9)(10)(11)(12)(13)(14)(15), harmful/hazardous use (16)(17)(18)(19), or dependence . The cut points for the DUDIT are sex specific and include no drug related problems (males 0-5, females 0-1), drug related problems (males 6-24, females 2-24), or heavily dependent on drugs (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44). Sleep was assessed via a question from the National Centre for Chronic Disease Prevention and Health Promotion, where participants reported their average hours of sleep in a 24-hr period [44].…”
Section: Health Behavioursmentioning
confidence: 99%